Analyzing Scope Creep Control in Information Technology Projects to Support Digital Strategy: A Case Study at PT Klik Sinergi Solusi - Kuswardini, Azizah; Pasaribu, Rina Djunita (The Eastasouth Management and Business, 2025)
Digital transformation has become a core component of modern business strategy, positioning information technology (IT) projects as key drivers of organizational innovation and efficiency. However, the success of digital strategies is highly dependent on an organization’s ability to manage project scope with discipline. One of the most persistent challenges is scope creep—the uncontrolled expansion of project scope without formal approval—which can disrupt timelines, overburden teams, and diminish both the quality and strategic relevance of project outcomes. This study aims to identify the root causes of scope creep, examine its impact on the implementation of internal digital projects, and propose adaptive and structured control strategies. The research was conducted at PT Klik Sinergi Solusi (KSS) using a qualitative case study approach. Data were collected through in-depth interviews with six project stakeholders across different roles, direct observation, and project documentation analysis, including backlog records, meeting notes, and scope change archives. The findings reveal that scope creep at KSS is driven by a combination of weak scope planning structures, the absence of effective change control mechanisms, inconsistent and undocumented communication, and an overly accommodating organizational culture toward user requests. As a result, projects suffer from delays, wasted effort, reduced output quality, and misalignment with the company’s digital strategy. The study also formulates six scope control strategies, including stronger scope baselines, regular validation forums, optimized use of project tools, and the development of a data-driven, assertive project culture. This research contributes to the theoretical discourse on digital project management and offers practical recommendations for designing scope control mechanisms that support the success of digital transformation initiatives.